2016
DOI: 10.22161/ijaers/3.11.11
|View full text |Cite
|
Sign up to set email alerts
|

An Approach of Automated Electronic Voting Management System for Bangladesh Using Biometric Fingerprint

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Election Commission (EC) of Bangladesh had piloted these machines for vote capture with great success indifferent local government election in Bangladesh [2], [3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Election Commission (EC) of Bangladesh had piloted these machines for vote capture with great success indifferent local government election in Bangladesh [2], [3].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies [4], [5] used Adhar card, conceptual design to link up the biometric data of Adhar card with e-voting machine. Sarkar et al [2] provided a brief discussion of existing e-voting systems, framework, and protocols. Recent developments of EVM in context of Bangladesh has been discussed and suggested some strategies to improve the security, accuracy of the existing design.…”
Section: Introductionmentioning
confidence: 99%
“…IoT based systems and robots are helping mankind in remote monitoring [10], remote sensing [11], disabled patient management [12], virus affected people management [13] and so on in all times [14] in secure way [15]. Embedded systems and IoT are helping hospitals [16], Agricultural Systems [17], energy generation [18], electronic voting [19] and bio-metric [20] security systems. Akhund et al [6] reported a 97.9% success rate to recognize hand gestures of disabled as well as virus-affected people to operate the robot.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An IoT based system is designed fo by [16]. EVS systems [17] are also using IoT and Robotics [18]. We can sense remote data with IoT based Robots [19].…”
Section: Literature Reviewmentioning
confidence: 99%